A educação física escolar na Revista de Educação Física (1932-1952): apropriações de Rousseau, Claparède e Dewey - Magda Terezinha Bermond (2007)
This study is an effort to understand on the Physical Education Magazine from 1932 to 1952, the relationship established between the proposal of practices and content oriented towards the classes of school Physical Education, and the pedagogical concepts of Jean - Jacques Rousseau, Edouard Claparède, and John Dewey. In order to achieve this purpose, two movements are made: the mapping out of the production of school Physical Education on the Magazine, and an analysis of this production, concerning the appropriations made by the theoreticians of pedagogical conceptions in the work of those authors. To achieve these objectives, there is a mobilization of the notions of appropriation and those of representation, as enunciated on Roger Chartiers proposals. The mapping out, shows that school Physical Education on the Magazine, incorporated knowledge from various areas, such as Pedagogy , Psychology, Anthropometry, Biotype, and Medicine, emphasizing a multidisciplinary characteristic for the discipline of Physical Education, as to what concerns the school environment. The analysis of these theoreticians, indicate that school Physical Education was produced by military authors from various patents, as well as civilians, with several functions, such as teachers, teaching inspectors, and doctors. The comparison between the works of Jean- Jacques Rousseau, Edouard Claparède and John Dewey, and the articles on school, indicate that their pedagogical conceptions were appropriated by the theoreticians as a theoretical support on the elaboration of proposals for the teaching of Physical Education in schools. Thus, the Physical Education Magazine, was one of the opening doors for the circulation of the new school ideas within the Brazilian Physical Education area, used by its editors/authors, as strategy (CERTEAU, 1994), for the consolidation of Physical Education as a practice to be inserted in schools, at this period.